LONG-TERM ACTIVITY OF RENIN-ANGIOTENSINALDOSTERONE AND SYMPATHO-ADRENAL SYSTEMS IN PATIENTS WITH PRIMARY MYOCARDIAL INFARCTION - V. A. Kokorin; N. V. Sytnik; A. V. Dudareva; N. A. Volov; V. A. Lusov (Российский кардиологический журнал, 2009)
.